Investigation of heat transfer effect on polymerase chain reaction - Kafafy, Raed Ismail (s.n, 2012)
This report presents the final results of the research project titled “Investigation of heat transfer effect of nanoparticles on PCR”. In this research we have demonstrated the effects of a novel material, graphene nano-flakes on PCR. The rationale behind the use of graphene flakes is its unique physical and heat transfer properties. A number of experimental results including the effect of graphene flakes on denaturation of DNA and annealing have been discussed. The preliminary results clearly show that enhanced heat transfer effect of nano-flakes augment PCR yield and ultimately overall enhancement in reaction efficiency.